Semar Mesem among Santri: A Phenomenological Study of Magical Practices - Sholahuddin Al Ayubi; Ursa Agnia; H.S. Suhaedi; Nouval Syamsu; Kholilullah Kholilullah (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2025)
This study examines an interesting phenomenon in the world of pesantren: the use of the magical practice